Does trade-off between child quantity and child quality exist in Malaysia? - Abdul Razak, Nor Azam; Abd Karim, Mohd Zaini; Abdul Hakim, Roslan (World Scientific Publishing Company, 2015)
This paper analyzed whether the child quantity-quality (CQQ) trade-off is applicable in the case of Malaysia.Utilizing the instrumental variable (IV) method, our analysis produces results that are consistent with the hypothesis that the trade-off is unlikely to be applicable to Malaysia as a whole due to the generous public provision of education. However, the results show that the CQQ trade-off exists for the high-income group.Taken together, if both a larger stock of human capital and population are desired, the government should continue to provide education for its people while at the same time maintain policies that stimulate growth.